Representing Islam in the Eyes of the Self and the Other: A Critical Discourse Analysis of Newspaper Articles - Resminingayu, Dewi Hermawati (UI Scholars Hub, 2013)
Since terrorism in Indonesia was associated to Moslem extremists, news regarding Islam has been mostly associated with those two aspects. In results, the concern of researches related to Islam in media only focuses on terrorism issue. Providing this background, this research is aimed to raise the issue related to Moslems and the Chinese minority in Indonesia, specifically in the celebration of Chinese New Year 2013 which is associated with Islamic issue. The data of this research are two newspaper articles. The first article is written by a journalist working for Agence France Presse (AFP) as the foreign media. Meanwhile, the other is written by The Jakarta Post which is the national media. The pivotal theory applied in this research is Critical Discourse Analysis (CDA) by Norman Fairclough. This theory comprises of two notions of analysis namely communicative event analysis and order of discourse analysis. Orientalism theory by Edward W. Said regarding the self and the other is also applied to analyze the socio-cultural context of the data. In this case, AFP represents the self, while The Jakarta Post is the other. After conducting thorough analysis, the findings disclose that the self represents Indonesian Islam negatively. In contrast, the other represents Indonesian Islam objectively